Blood plasma nonessential aminoacids of stable and unstable stenocardia patients - Lyzogub, V.G.; Zavalskaya, T.V.; Bogdan, V.V.; Zhornichenko, D.M. (Reports of the National Academy of Sciences of Ukraine, 2015)
The study involves patients with stable and unstable stenocardia. The ion exchange liquid-column chromatography method is used. In unstable stenocardia patients as compared with stable ones, a significant increase in the content of such aminoacids as proline, ornithine, glycine, serine and taurine is revealed. A decrease in the content of alanine, glytamine, and cysteine is found.